اثر ادارة التكاليف على تحسين اداء الخدمات الصحية-دراسة حالة - جمال لعموري (university of eloued جامعة الوادي, 2025)
"الملخص: تهدف هذه الدراسة إلى معرفة مدى تأثير إدارة التكاليف على تحسين أداء الخدمات الصحية في المؤسسة العمومية االستشفائية لوالية الوادي، واستخدمنا المنهج الوصفي التحليلي مع دراسة ميدانية متمثلة في قائمة استبيان موزعة على 80 فردا من عينة الدراسة، حيث توصلت الدراسة إلى أنه يتوجب التحكم الجيد في أبعاد تكاليف الجودة باإلضافة إلى وجوب اتباع استراتيجية واضحة من طرف المؤسسة الصحية من أجل تحسين أداء الخدمات الصحية. "This study aims to determine the extent of the impact of cost management on improving the performance of health services in the public hospital institution of the state of El-Oued. We used the descriptive analytical approach with a field study represented by a questionnaire distributed to 80 individuals from the study sample. The study concluded that the dimensions of quality costs must be well controlled, in addition to the necessity of following a clear strategy by the health institution in order to improve the performance of health services."
Keywords: إدارة التكاليف; الخدمات الصحية; اإلدارة الصحية; تكاليف الجودة.; Cost management; Health Services; Health Management; Quality Costs.